1997
DOI: 10.1038/sj.ijo.0800536
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of weight maintenance in women after diet-induced weight reduction

Abstract: OBJECTIVE: Assessment of determinants for relatively successful weight maintenance in women after diet-induced weight reduction. DESIGN: Subjects followed two weight cycles over two years, each cycle starting with a Very Low Energy Diet (VLED) (2.8 MJad), in a free-living situation. They completed the Herman Polivy Restraint Questionnaire and the Three Factor Eating Questionnaire twice, that is, before and during the ®rst VLED. SUBJECTS: Twenty seven obese women, body mass index (BMI) (28±38 kgam 2 ), age (19±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
74
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(92 citation statements)
references
References 13 publications
17
74
1
Order By: Relevance
“…In contrast to our results and others [17], similar trials performed in non-diabetic, obese individuals have reported long-term weight loss principally due to reductions in fat mass [21,22]. This preferential loss of LBM in Type 2 diabetes may be due to a higher whole-body proteolytic rate associated with moderate hyperglycaemia [23].…”
Section: Discussioncontrasting
confidence: 98%
“…In contrast to our results and others [17], similar trials performed in non-diabetic, obese individuals have reported long-term weight loss principally due to reductions in fat mass [21,22]. This preferential loss of LBM in Type 2 diabetes may be due to a higher whole-body proteolytic rate associated with moderate hyperglycaemia [23].…”
Section: Discussioncontrasting
confidence: 98%
“…The success of weight loss maintenance has been shown to be dependent on an increase in dietary restraint during weight reduction phase. [9][10][11] In our previous study, 5 the weight loss in obese women in response to 4-week VLCD treatment combined with cognitive behavioral therapy was associated with a significant increase in restraint score and a significant decrease in disinhibition and hunger scores of the EI, as well as with a significant decrease in the Beck depression score.…”
Section: Discussionmentioning
confidence: 80%
“…The relationship between EI scores and weight change has been evaluated in the dietary treatment of obesity, 7 the treatment of severely obese patients by bariatric surgery 8 as well as in weight maintenance after diet-induced weight reduction. [9][10][11] Psychological and behavioral predictors of weight loss have also been evaluated in the context of pharmacological treatments for obesity, including fenfluramine, phentermine, mazindol and caffeine plus ephedrine, 12 usually administered as combined therapy (fenfluramine þ phentermine, fenfluramine þ mazindol). Baseline scores of two items of the EI, perceived hunger and dietary restraint, appeared important factors in the prediction of weight loss after 6 and 12 months of drug treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The risks associated with many of these comorbid conditions may be reduced with modest weight loss. Weight control methods often produce short-term success, but sustained weight maintenance is difficult to reach (Westerterp-Plantenga et al, 1998;. Moreover, the increasing prevalence of obesity (Kuczmarski et al, 1994) requires preventive treatments of obesity.…”
Section: Introductionmentioning
confidence: 99%